Hybrid surgery for imminent rupture of superior mesenteric artery aneurysms - Yuta Miyano, MD; Hiroshi Mitsuoka, PhD; Takahiro Suzuki, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
A case of a superior mesenteric artery aneurysm presented with an impending rupture. The aneurysm was located in the right side branch of the superior mesenteric artery. The patient underwent an emergency hybrid procedure, which included aneurysm embolization and exclusion of the aneurysm with an endoluminal stent graft. The blood supply to the right side branch was restored by bypass grafting with an autologous vein graft. The postoperative course was uneventful with no evidence of mesenteric ischemia. Postoperative computed tomography angiography confirmed complete aneurysm exclusion and sac size reduction, as well as patency of the stent graft and bypass.